Akuntabilitas dan Transparansi Laporan Keuangan Pada Organisasi Pengelola Zakat: Studi Komparatif di BAZ dan LAZ Yogyakarta - Wulaningrum, Puspita Dewi; Pinanto, Amin (Jati: Jurnal Akuntansi Terapan Indonesia, 2020)
The research aims at learning about the accountability and transparency as well as the accounting policy on the financial statement of BAZNAS Kota Yogyakarta and Lazismu Kota Yogyakarta in managing zakat, infaq, and shodaqoh funds based on PSAK Number 109. The research used qualitative descriptive method. The data were collected through interviews, observations, and documentation. The analysis method of the research used descriptive qualitative approach, multiple case study, and comparative research. The research result indicates that BAZNAS Kota Yogyakarta has been accountable and transparent in preparing the annual financial statements which comply with PSAK Number 109. This is proven by the complete financial statement components, separate presentation of non-halal funds, on-time statement submission, and that the statements are audited by external institutions. Meanwhile, Lazismu Kota Yogyakarta has not been accountable and transparent based on PSAK 109. This is due to the incomplete financial statements and the fact that the statements have not been published in printed and digital media.